Implementasi Marketing Mix sebagai Strategi Pemasaran Pendidikan di Madrasah Aliyah Tahfidz Al-Qur’an Al-Ishlah - Hindun Masruroh; Hanifah Miftahur Rizki (Pascasarjana IAIN Ponorogo, 2025)
Competition between educational institutions, especially the private sector in order to get new students is very tight, this can be seen from the many educational institutions that implement marketing strategies to attract as many students as possible. This study aims to reveal the implementation of marketing strategies for educational services based on management theory and marketing mix at Madrasah Aliyah Tahfidz Al Ishlah. This is motivated by efforts to create a quality Islamic educational institution, so that it can compete with other educational institutions. The type of qualitative research method is descriptive, the research subjects taken are the Head of Madrasah, Deputy Head of Public Relations, Deputy Head of Student Affairs, Deputy Head of Curriculum, Operators, and Students. By conducting data collection techniques used by researchers using observation, interviews, and documentation. The results of this study are the application of marketing mix service marketing strategies at Madrasah Aliyah Tahfidz Al Ishlah which emphasizes 7P, namely product, price, place, promotion, people, physical evidence, and process. The results of this study indicate that: first, the marketing strategy of educational services to improve the quality of education at Madrasah Aliyah Tahfidz Al Ishlah using the management function, there are four stages, namely planning, organizing, implementing and evaluating. Second, the implementation of the marketing strategy of educational services at Madrasah Aliyah Tahfidz Al Ishlah through the marketing mix, namely; product, place, price, promotion, people, physical evidence, and process. The competitiveness of Madrasah Aliyah Tahfidz Al Ishlah is quite good, this can be seen from the data on the increase in the number of students.